Evaluación del nivel cognitivo en la cultura de seguridad laboral de los trabajadores de la empresa florícola Rosas del Cotopaxi CIA. LTDA. Y diseño de un módulo de capacitación en seguridad laboral. - Pacheco Guerrero, Freddy Washington (2011)
The floricultural business of Cotopaxi Roses Limited Company dedicated to the cultivating production, postharvest, storage, commercialization and transport of fresh cut flowers, using the human labor in the productive process, the same that is found vulnerable on the basis of the dangers that affect the security of the workers. By virtue of this, it is necessary to conduct a survey to staff working in the flower company to assess their cognitive level of workplace safety culture. With that respect, it is necessary to realize a survey amongst the personnel that works in the floricultural business in order to evaluate their cognitive level in the security labor culture. By taking into account the evaluation, which will be realized by workers, the processes that endanger the workers’ physical, mental, and health would be identified. The results of the evaluation will be the foundation of the design of the training module that will be an educational tool to promote the professional standard improvement. This will lead to cognitive development in occupational safety, helping to provide basic knowledge of legal and administrative rules that will help to minimize the likelihood of risk success in all jobs. The research is paradigmatically qualitative and quantitative type, with a feasible proposal project, using the field research methodology, documentation and bibliography. The probability sample is 88.33% of total staff working in the flower company, the results of the survey will be evaluated quantitatively, and the content of the training module will be assessed by qualitative means. The training module on job security is a technical, educational and preventive social-cultural context that will help to the Cotopaxi Roses limited company. For the future to implement systematic and integrated occupational health and safety.